The Transformation of Intimacy: The Case of Birth Partners - Bartáková, Petra (Lidé města, 2016)
This article focuses on the transformation of intimacy, in particular on the experiences of Czech mothers who gave birth with the support of professional and non-professional birth partners. In our area, all births in the last century have shifted from the domestic environment, full of various ritual practices, to the institutional environment of maternity hospitals. In this sense, the labouring woman is separated from related persons. During the 1970s, obstetric care changed under the influence of the rising commercialisation and individualisation of obstetric care. Maternity hospitals started to open to the public and to also organise visits in delivery rooms, as well as in post-natal rooms, and to tolerate the presence of accompanying persons at the delivery. In the Czech environment, similar changes in obstetrics appeared after 1989. Relationships between clients (parents) and professional accompanying persons (doulas, independent midwives) can involve contemporary practices of intimacy such as self-disclosure, physical contact, and practical care. This “new” phenomenon of birth partners blurs the boundaries between an intimate relationship and a commercial transaction. My work primarily builds upon social studies focused on the transformation of intimacy in modernity and human reproduction, in particular, the theoretical foundations of the anthropology and the sociology of childbirth. The goal is to elucidate the processes of the transformation of intimacy, which are characteristic of temporary intimacy, through analysing eighteen semi-structured and narrative interviews given by birth partners and mothers who had a birth companion.